Idiopathic localised dilatation of the intestine in adults - Rotigliano, Niccolò (BMJ Case Rep, 2019)
Idiopathic localised dilatation of the intestine (ILDI) presenting in adults is rare and difficult to diagnose. Only 18 cases have been reported in the literature. We report a case of a 32-year-old woman presenting with abdominal pain and intermittent small bowel obstruction. After detailed radiological studies, the patient, known for Crohn’s disease, was scheduled for laparoscopy in the suspicion of small bowel stricture. A localised dilatation of the ileum was found intraoperatively and subsequently resected. A systematic review of this rare pathology in adults is carried out. ILDI should be part of the differential diagnosis in patients with unexplained abdominal pain or gastrointestinal bleeding in the presence of segmental dilatation of the intestine. Surgical resection is the treatment of choice.